English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

please explain...

2007-10-18 08:49:54 · 8 answers · asked by me 3 in Science & Mathematics Mathematics

I feel dumb now....one of those duh moments. Thanks a lot.

2007-10-18 08:54:48 · update #1

8 answers

(y^2 + 8)(y^2 - 3) = 0

2007-10-18 08:53:16 · answer #1 · answered by Anonymous · 1 0

if x = y^2, then your equation becomes this:

x^2 + 5x - 24 = 0

Can you solve it now? You have to find the factors of 24 whose difference is +5. (You have to do the difference because 24 is negative -- if it were positive, you would have to do the sum)

1 & 24 ----- the difference is +/- 23
2 & 12 ----- the difference is +/- 10
3 & 8 ---- the difference is +/- 5 <=== there you go
4 & 6 --- the difference is +/- 2

8 - 3 = +5 <== so I want +8 & -3
3 - 8 = -5

(x + 8)(x - 3)=0

substitute the y^2 back in and get

(y^2 + 8)(y^2 - 3) = 0

I hope that helps!

2007-10-18 16:01:16 · answer #2 · answered by nc 3 · 0 0

(y^2 + 8)(y^2 -3) = 0

2007-10-18 15:55:12 · answer #3 · answered by T 5 · 0 0

y^4 + 5y^2 - 24 = (y^2 + 8)(y^2 - 3). If you want to go further, you'll have to use square roots on the right-hand factor: y^2 - 3 = (y + sqrt(3))(y - sqrt(3)).

2007-10-18 15:55:12 · answer #4 · answered by TurtleFromQuebec 5 · 2 0

(y^2 + 8)(y^2 - 3)

2007-10-18 15:55:15 · answer #5 · answered by papastolte 6 · 1 0

(y^2 + 8)(y^2 - 3)

2007-10-18 15:54:13 · answer #6 · answered by fcas80 7 · 1 0

Hi, check out this websight it might have some answers and has got some example on how to solve problems like it. hope this helps a little.


http://www.mathnstuff.com/math/algebra/asystem.htm

2007-10-18 15:59:43 · answer #7 · answered by git_errr_dun 1 · 0 0

( y ² + 8 ) ( y ² - 3 ) = 0
y = ± i √(8) , y = ±√3

2007-10-18 18:04:54 · answer #8 · answered by Como 7 · 0 0

fedest.com, questions and answers